GAMBARAN PENGETAHUAN DAN EVALUASI CARA PENGGUNAAN INSULIN PEN PASIEN DIABETES MELLITUS DI RUMAH SAKIT BHAYANGKARA POLDA BENGKUL - Rikomah, Setya Enti (Universitas Hang Tuah, 2024)
Treatment for diabetes with insulin is given using an insulin pen. Pen insulin can be used alone by the patient without requiring trained personnel. The patient's incomprehension in carrying out therapy is one of the causes of therapy failure, due to the lack of knowledge and understanding of the patient about the drug, everything related to the use of drugs for treatment.The purpose of the study was to determine the knowledge based on the characteristics of respondents, evaluation of insulin use pen, injection area, storage area, side effects. The study was conducted by distributing questionnaires as primary data and sampling using purposive sampling method. Respondents were patients with diabetes mellitus who used insulin pen in poly disease in Bhayangkara Hospital. Data processed descriptively displayed with tables and graphs.The results of the study were respondents with good knowledge, namely undergraduate 10 respondents (15.87%), civil servants and other jobs (pensioners, irt, students) each of 9 respondents (14.29%), women15 respondents (23.81%), age 18 - 65 years 19 respondents (30.61%). Fast action insulin and combination of 17 respondents (26.98%), novorapid 15 respondents (23.81%), no oral drugs 44 respondents (69.84%), frequency 2 times a day, novomix 14 respondents (22 , 22%), 10-15 units 13 respondents (20.63%), insulin use> 1 year 27 respondents (42.86%), did not cause symptoms 57 respondents (90.48%). The use of the abdominal and arm areas of 23 respondents (35.51%), storing in the refrigerator 32 respondents (50.79%), did not cause side effects 58 respondents (92.07%)